Identifikasi dan Kuantifikasi Metabolit Bakteri Pelarut Fosfat dan Pengaruhnya terhadap Aktivitas Rhizoctonia solani pada Tanaman Kedelai - Setiawati, Tri Candra; Mihardja, Paniman Asna (JOURNAL OF TROPICAL SOILS, 2008)
Phosphate solubilizing bacteria (PSB) metabolites are organic acids, phosphomonoesterase enzyme (alkaline phosphatase) and antibiotic, which is able to dissolve insoluble phosphate. Phosphate solubilizing bacteria used in this study was expected to suppress Rhizoctonia solani attacks. This experiment was aimed at (1)  identifiying and quantifying  PSB metabolites, and (2) examining their capability as biocontrol agent for Rhizoctonia solani in vitro and hydroponics soybean. This study was conducted in three stages. The first stage of this study was culturing two PSB isolates (Pseudomonas putida 27.4B and Pseudomonas diminuta) in the Pikovskaya medium to analyze their metabolites. The second and third stage of this study was testing the antagonist of two bacteria to suppressed R. solani activity, which was conducted in vitro, and in hydroponics medium soybean as indicator plant. The results showed that P. putida 27.4B and P. diminuta produced organic acids i.e.: citrate, formic, succinic, acetic, propionate, butyrate, and oxalate. The totals of organic acids from each bacterium were 70,3 mg.kg-1 and 61,9 mg.kg-1. Production of alkaline phosphatase enzyme in Pikovskaya medium of P. Putida27.4B was 11,71 μg pNP .mL-1.h-1 and P. diminuta was 24,04  μg pNP.mL-1.h-1. Concentration of this enzyme in soil medium was higher than that in Pikovskaya medium with 26,27 μg pNP.g-1.h-1 and 39,03 μg pNP.g-1.h-1 respectively. This study also showed that total concentration of antibiotics (tetracycline, oxitetracycline and penicillin) produced by the PSB, were 3,2 μg.mL-1 (P. putida 27.4B) and 10,96 μg.m1-1 (P. diminuta), respectively. The results from second stage of this study showed that by using in vitro, the reduced growth of  R. solani was observed 58,35% with P. putida 27.4B and 41,96% with P. diminuta. In addition, inoculations of PSB in hydroponics medium reduced the fungal pathogenesis from 10,71% to 21,42% of pre and post emergence damping-off. Visually, the symptom of pathogen attack appeared within the period of  2 untill 14 days after infection.